Anthropometric evaluation of body composition in ballet dancers. A longitudinal study - Maria Elena Díaz Sánchez; Julieta Aréchiga Viramontes; Hamlet Betancourt León (Universidade Federal de Santa Catarina, 2008)
The body of the adolescent dancer is the result of morphological, physiological and behavioral adaptations due to specific physical training. For the ballet master, body weight is irrelevant to evaluating the technical and artistic performance and beauty of a figure. All ballet dancers must have bodies that conform to the canon of international ballet in order to be able to perform in public. The purpose of this study is to describe the changes in the body composition of dancers at the Cuban National School of Ballet between two points in their training process. This was a longitudinal study of 54 girls and 40 boys, aged between 15 and 20 years old. An anthropometric protocol of 6 measurements was employed in order to determine body composition using the Durnin and Rahaman method for females and the Parizková and Buzková method for males. The main results demonstrate signifi cant increases in both weight and height for age in both sexes, and it was observed that height growth velocity decreased with age. The female dancers exhibited stable body fat percentages for all ages while male dancers signifi cantly reduced this percentage from one year to the next. The female students exhibited higher mean percentage body fat values than the normal range established in Cuba for elite athletes from competitive artistic sports and professional dancers, while the male students exhibited body fat percentages that were similar to these specialized groups. Resumo El cuerpo humano del bailarín adolescente es resultado de las adaptaciones orfológicas-fi siológicas y conductuales de un entrenamiento físico particular. Para los maestros de ballet el peso corporal no es relevante en la evaluación técnica-artística y de belleza de la fi gura del danzante. Cada bailarín tiene que cumplir con los cánones internacionales de fi gura del ballet para presentarse en el escenario artístico. El objetivo de esta investigación es describir las variaciones de la composición corporal de los bailarines de la Escuela Nacional de Ballet de Cuba en dos momentos del proceso de entrenamiento. Se analizaron a través de un estudio longitudinal 54 bailarinas y 40 bailarines con edades entre 15 y 20 años. Se aplicó un protocolo antropométrico de 6 mediciones para estimar la composición corporal, empleándose las ecuaciones de Durnin y Rahaman, sexo femenino y Parizková y Buzková, sexo masculino. Los bailarines manifestaron incrementos signifi cativos de peso y estatura; la velocidad de crecimiento de la estatura disminuyó con la edad para los dos sexos. En las bailarinas de todos los grupos etarios no se encontraron diferencias signifi cativas en el porcentaje de la masa grasa de un año a otro, mientras todos los bailarines disminuyeron significativamente los valores porcentuales grasos en el mismo intervalo del estudio. Las féminas estudiantes presentaron valores promedios de porcentaje graso superiores al rango establecido en ejecutantes cubanos de deportes de arte competitivo y ballet profesional; los varones estudiantes registraron porcentajes grasos en rangos similares a los informados en esas poblaciones especializadas.